PEMAKAIAN CO2 SEBAGAI REFRIGERAN - Adriansyah, Willy; Bredesen, Arne M; Neksa, Petter (Mesin, 1997)
In the present situation there is a tendency to avoid as far as possible the use of the synthetic substances as refrigerant which can destroy ozone layer and increase average contribute to the A much more safe philosophy must be to revert to natural refrigerants, substances which are already present in our environment. The use of C02 as refrigerant is one attempt to this approach. This new refrigeration technology use special cycle called âLorentzen Cycle". Â Lorentzen s invention opened a wide way to enhance the refrigeration technology and brought a lot of applications that can use this new cycle. This paper try to explain the basic principle ofâLorentzen Cycleâ and one of such applications which has being developed at Norwegian University of Science and Technology.